Re-Imagine! Business Excellence in a Disruptive Age - Tom Peters (USA DK, 2003)
More than just a how-to book for the 21st Century, Re-imagine! is a call to arms -- a passionate wake-up call for the business world, educators, and society as a whole. Focusing on how the business climate has changed, this inspirational book outlines how the new world of business works, explores radical ways of overcoming outdated, traditional company values, and embraces an aggressive strategy that empowers talent and brand-driven organizations where everyone has a voice.
Keywords: Business; Management; Leadership; Nonfiction; Personal Development; Productivity; Education; HRM: Contemporary Issues (HRM2074-N)